MODEL FOR DEVELOPING COMPETENCY OF COMMUNITY ENTERPRISE ENTREPRENEURS IN PRACHUAP KHIRI KHAN PROVINCE - สมพงษ์ โชติรส; เผือกบัวขาว สาโรช (Academic Journal Phranakhon Rajabhat University, 2019)
The purposes of this research were: 1) to study the competency of community enterprise entrepreneurs, 2) to investigate the success of community enterprise entrepreneurs, 3) to examine the relationship between the competency and success of community enterprise entrepreneurs, and 4) to propose the model for developing competency of community enterprise entrepreneurs in Prachuap Khiri Khan Province. The mixed methodology was applied in this study. The questionnaire was used for collecting quantitative data from 135 community enterprise entrepreneurs in Prachuap Khiri Khan Province. The quantitative data were analyzed by computing percentage, mean, standard deviation, and Pearson’s Correlation Coefficient. The in-depth interview was used for collecting qualitative data from 14 informants, personnel involving in proceeding community enterprises and One Tambon, One Product (OTOP). The research results were as follows: 1) the competency of community enterprise entrepreneurs was overall at a high level. The aspect with the highest mean was motive. The other aspects with the lower means were, ranked in descending order of their means, trait, knowledge, self-concept, and skill, 2) the success of community enterprise entrepreneurs was overall at a moderate level. The aspect with the highest mean was competitive aggressiveness. The other aspects with the lower means were, ranked in descending order of their means, self-confidence, proactiveness, creativeness, and risk taking, 3) there was a positive relationship, with correlation coefficient with statistical significance at the 0.01 level between the competency and success of community enterprise entrepreneurs, and 4) the model for developing competency of community enterprise entrepreneurs, to drive the development of community enterprise entrepreneurs’ competency to be able to become self-reliant, was A-SAP model consisting of 3 aspects as follows: S (Survey of entrepreneurs’ needs), A (Action Plan or preparing entrepreneur development plan according to their needs), and P (Practice or implementation of entrepreneur development plan).